Method for design of two-level system of active shielding of power frequency magnetic field based on a quasi-static model - Kuznetsov, B. I.; Kutsenko, A. S.; Nikitina, T. B.; Bovdui, I. V.; Kolomiets, V. V.; Kobylianskyi, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Development of method for design a two-level active shielding system for an industrial frequency magnetic field based on a quasistatic model of a magnetic field generated by power line wires and compensating windings of an active shielding system, including coarse open and precise closed control. Methodology. At the first level rough control of the magnetic field in open-loop form is carried out based on a quasi-static model of a magnetic field generated by power line wires and compensating windings of an active shielding system. This design calculated based on the finite element calculations system COMSOL Multiphysics. At the second level, a stabilizing accurate control of the magnetic field is implemented in the form of a dynamic closed system containing, in addition plant, also power amplifiers and measuring devices of the system. This design calculated based on the calculations system MATLAB. Results. The results of theoretical and experimental studies of optimal two-level active shielding system of magnetic field in residential building from power transmission line with a «Barrel» type arrangement of wires by means of active canceling with single compensating winding are presented. Originality. For the first time, the method for design a two-level active shielding system for an power frequency magnetic field based on a quasi-static model of a magnetic field generated by power line wires and compensating windings of an active shielding system, including coarse open and precise closed control is developed. Practical value. It is shown the possibility to reduce the level of magnetic field induction in residential building from power transmission line with a «Barrel» type arrangement of wires by means of active canceling with single compensating winding with initial induction of 3.5 µT to a safe level for the population adopted in Europe with an induction of 0.5 µT

Розробка методу проектування дворівневої системи активного екранування для магнітного поля промислової частоти на основі квазістатичної моделі магнітного поля, яке створюється проводами лінії електропередач і компенсаційними обмотками системи активного екранування, включаючи грубе розімкнуте і точне замкнуте управління. Методологія. На першому рівні програмне керування магнітним полем в розімкнутій формі здійснюється на основі квазістатичної моделі магнітного поля, яке створюється проводами лінії електропередач і компенсаційними обмотками системи активного екранування. Це проектування виконується на основі розрахункової системи скінчених елементів COMSOL Multiphysics. На другому рівні реалізовано стабілізуюче управління магнітним полем в формі динамічної замкнутої системи, що містить, крім об’єкту управління, також підсилювачі потужності та вимірювальні пристрої. Це проектування виконується в розрахунковій системі MATLAB. Результати. Наведено результати теоретичних та експериментальних досліджень оптимальної дворівневої системи активного екранування магнітного поля з однією компенсуючою обмоткою для житлового будинку від дії магнітного поля лінії електропередачі з розташуванням проводів типу «бочка». Оригінальність. Вперше запропоновано метод проектування дворівневої системи активного екранування магнітного поля промислової частоти на основі квазістатичної моделі магнітного поля, яке створюється проводами лінії електропередач і компенсаційними обмотками системи активного екранування, в вигляді грубого розімкненого і точного закинутого управління. Практична цінність. Показано можливість зниження рівня індукції магнітного поля в житловому будинку від магнітного поля лінії електропередач з розташуванням проводів типу «бочка» за допомогою однієї компенсуючої обмотки, з початкової індукції в 3,5 мкТл до безпечного рівня для населення, який прийнятий в Європі, з індукцією в 0,5 мкТл.
Keywords: overhead power line; magnetic field; quasi-static model; system of active shielding; computer simulation; experimental research; повітряна лінія електропередачі; магнітне поле; квазістатична модель; система активного екранування; комп'ютерне моделювання; експериментальні дослідження